An infant with refractory cytomegalovirus‐induced thrombocytopenia. Issue 1 (17th December 2019) - Uemura, Suguru; Mori, Takeshi; Nino, Nanako; Sakakibara, Nana; Takafuji, Satoru; Myojin, Shota; Takami, Yuichi; Morioka, Ichiro; Nishimura, Noriyuki; Kugo, Masaaki; Iijima, Kazumoto
Abstract: The present case underscores the importance of considering the association of severe thrombocytopenia or immune thrombocytopenia with cytomegalovirus (CMV) infection because CMV‐induced thrombocytopenia occasionally requires antiviral therapy. Abstract : The present case underscores the importance of considering the association of severe thrombocytopenia or immune thrombocytopenia with cytomegalovirus (CMV) infection because CMV‐induced thrombocytopenia occasionally requires antiviral therapy.